2017
DOI: 10.1002/ccr3.1193
|View full text |Cite
|
Sign up to set email alerts
|

Mexican case report of a never‐treated Laron syndrome patient evolving to metabolic syndrome, type 2 diabetes, and stroke

Abstract: Key Clinical MessageGlucose and lipid profile together with blood pressure should always be considered for low sera‐IGF‐1 patients. Even when adulthood is reached, IGF‐1 therapy in these patients should be pursued as metabolic and protective cellular effects could be triggered. Real incidence of growth hormone insensitivity is still to be uncovered.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…There were no reports of dyslipidemia in LS children patients. However, there was a case of a Mexican female with untreated LS who developed metabolic syndrome at the age of 53 years [ 5 ]. It may result from GH/IGF-1 deficiency that causes disorders in adipose tissue metabolism and obesity that progress with age [ 6 ].…”
Section: Discussionmentioning
confidence: 99%
“…There were no reports of dyslipidemia in LS children patients. However, there was a case of a Mexican female with untreated LS who developed metabolic syndrome at the age of 53 years [ 5 ]. It may result from GH/IGF-1 deficiency that causes disorders in adipose tissue metabolism and obesity that progress with age [ 6 ].…”
Section: Discussionmentioning
confidence: 99%
“…For Latin Americans, the E180 polymorphism is the most common due to a mass migration to Ecuador[21]; nevertheless, the E180 polymorphism has been found in Brazil, Argentina, and Mexican-descendants in the United States[4]. Recently, in Monterrey, Mexico, three patients were identified with LS, and the key mutations that were identified as possible causes were not of GHR[5-7]. Here, we demonstrate that the LS in the parents was associated with the del5-6 of GHR.…”
Section: Discussionmentioning
confidence: 99%
“…During development, the establishment of a proper intrauterine environment for fetal development is mandatory, a situation where IGF-1 plays a key role. To date, several case reports in women have shown that partial IGF-1 deficiency might be involved in alterations in the reproductive system and the attainment and maintenance of pregnancy [ 38 , 39 , 40 ], and also its implications in metabolism, which could alter the metabolism of xenobiotic substances such as ethanol. For this reason, the development of an animal model that resembles the physiological alterations due to partial IGF-1 deficiency is crucial for studying the mechanisms and molecular targets involved in its development, especially in critical periods such as pregnancy.…”
Section: Discussionmentioning
confidence: 99%